Airway response to acute mechanical stress in a human bronchial model of stretch - Faisy, Christophe (BioMed Central, 2011)
INTRODUCTION: Lung inflation may have deleterious effects on the alveoli during mechanical ventilation. However, the consequences of stretch during excessive lung inflation on basal tone and responsiveness of human bronchi are unknown. This study was undertaken to devise an experimental model of acute mechanical stretch in isolated human bronchi and to investigate its effect on airway tone and responsiveness. METHODS: Bronchi were removed from 48 thoracic surgery patients. After preparation and equilibration in an organ bath, bronchial rings were stretched for 5 min using a force (2.5 × basal tone) that corresponded to airway-inflation pressure > 30 cm H(2)O. The consequences of stretch were examined by using functional experiments, analysis of organ-bath fluid, and ribonucleic acid (RNA) isolation from tissue samples. RESULTS: Following removal of the applied force the airways immediately developed an increase in basal tone (P < 0.0001 vs. paired controls) that was sustained and it did so without significantly increasing responsiveness to acetylcholine. The spontaneous tone was abolished with a Rho-kinase inhibitor and epithelium removal, a leukotriene antagonist or nitric oxide synthase inhibitors reduced it, whereas indomethacin, sensory nerve inhibitors or antagonists for muscarinic, endothelin and histamine receptors had no effect. Stretch enhanced leukotriene-E(4 )production during the immediate spontaneous contraction of human bronchi (P < 0.05). Moreover, stretch up-regulated the early mRNA expression of genes involved in wingless-type mouse mammary tumor virus integration-site family (WNT)-signaling and Rho-kinase pathways. CONCLUSIONS: Stretching human bronchi for only 5 min induces epithelial leukotriene release via nitric oxide synthase activation and provokes a myogenic response dependent on Rho-kinase and WNT-signaling pathways. From a clinical perspective, these findings highlight the response of human airway to acute mechanical stress during excessive pulmonary inflation.